PERJANJIAN PENGIKATAN JUAL BELI (PPJB) DALAM TRANSAKSI PERALIHAN HAK ATAS TANAH DAN ATAU BANGUNAN - Alusianto Hamonangan; Mhd. Taufiqurrahman; Rosma Mediana Pasaribu (JURNAL RECTUM: Tinjauan Yuridis Penanganan Tindak Pidana, 2021)
The process of transferring land rights based on the power of attorney to sell made by a notary is 3 months until the expiration of the principal credit agreement. In general, if the SKMHT is not upgraded to APHT within a certain time, then the SKMHT becomes null and void within 1 month after it is given. This research uses normative juridical, namely reviewing the laws and regulations. The conclusion is that a power of attorney to impose Mortgage is not immediately followed up with the making of a Deed of Granting Mortgage by the bank within a certain period of time specified in the Mortgage Law. If there are signs that the debtor will default, the position of SKMHT is changed to APHT and registered at the National Land Office so that it meets the requirements for the principles of speciality and publicity. This condition makes SKMHT in Article 15 UUHT upgraded to APHT in order to have executorial power over the objects guaranteed by the debtor.